Pemberdayaan Perempuan Bidang Pemasaran Untuk Produk Usaha Kecil Di Rukun Warga (RW) VI Kelurahan Sampangan, Kecamatan Gadjah Mungkur Kota Semarang - Maskur, Ali; Nawatmi, Sri; Purwatiningtyas, P; Yunianto, Askar; Budi, Mulyo (LPPM STIKOM Tunas Bangsa, 2024)
The World Economic Forum (WEF) has released the Global Gender Gap Report 2022. The report examines gender inequality in four areas, namely, political empowerment, economic participation and opportunities, educational attainment and health and survival. In this year's WEF report, Indonesia generally obtained a GII score of 0.697 and was ranked 92nd out of 146 countries. The aim of this service is to help empower women through outreach activities regarding the marketing of small business products in order to increase their role in helping the family economy. It is hoped that an understanding of marketing and its strategies will motivate the women of RW VI, Sampangan Village, Gadjah Mungkur District, Semarang City, to enter the business world. Understanding product marketing is very important to increase income from the business that will be carried out..